2013
DOI: 10.1097/hjh.0b013e3283652c61
|View full text |Cite
|
Sign up to set email alerts
|

Precise assessment of noncompliance with the antihypertensive therapy in patients with resistant hypertension using toxicological serum analysis

Abstract: We conclude that the evaluation of antihypertensive drugs concentrations is a useful and precise method for assessment of noncompliance in patients with resistant hypertension. This evaluation is useful before starting the diagnostic work-up of secondary forms of hypertension and before assignment patients into protocols with new therapy modalities such as renal denervation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
75
2
12

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(96 citation statements)
references
References 27 publications
7
75
2
12
Order By: Relevance
“…The minimal variation and relatively high rates of self-management reported when the Hill-Bone measurement instrument was administered to our study population at baseline, combined with the findings of two subsequent publications about the psychometric properties of the Hill-Bone [24,25], suggest that the tool may not be an ideal research instrument. The current literature indicates that about 50% of patients traditionally classified with resistant hypertension are effectively nonadherent [26,27]. In contrast, our study participants' baseline compliance score on the Hill-Bone medication subscale range was 11.5-11.7 out of a potential range of 9-28 with lower scores indicating greater adherence, suggesting a far higher rate of medication compliance than probable by the fact that all patients were selected because their BP was not controlled.…”
Section: Discussioncontrasting
confidence: 51%
“…The minimal variation and relatively high rates of self-management reported when the Hill-Bone measurement instrument was administered to our study population at baseline, combined with the findings of two subsequent publications about the psychometric properties of the Hill-Bone [24,25], suggest that the tool may not be an ideal research instrument. The current literature indicates that about 50% of patients traditionally classified with resistant hypertension are effectively nonadherent [26,27]. In contrast, our study participants' baseline compliance score on the Hill-Bone medication subscale range was 11.5-11.7 out of a potential range of 9-28 with lower scores indicating greater adherence, suggesting a far higher rate of medication compliance than probable by the fact that all patients were selected because their BP was not controlled.…”
Section: Discussioncontrasting
confidence: 51%
“…In all of these studies carried out in TRH or hypertensive patients with insufficient BP control, LC‐MS/MS was used to measure the drug levels, allowing a comparison of adherence rates. The definition of partial nonadherence, however, varies widely from “at least one or more substances missing” to “fewer than prescribed” or is not described in detail at all 14, 15, 16, 17. In our study, we used only 1 antihypertensive substances missing for the definition of partial adherence.…”
Section: Discussionmentioning
confidence: 99%
“…Electronic methods of adherence monitoring (ie, computerized records of pharmacy prescription or electronic monitoring of pill box opening) may be considered reliable alternatives, but it remains subject to the patient's behavior whether the removed pills are indeed ingested 1, 12, 13. Recently, toxicological urine analysis of the compounds or their metabolites has gained increasing interest 14, 15, 16, 17. These biochemical analyses represent spot assessments of adherence but are subject to the “white coat adherence” effect 18, 19.…”
Section: Introductionmentioning
confidence: 99%
“…1 Recent studies from our group and others have reported a high prevalence of non-adherence to antihypertensive medications among patients with a-TRH (50-60%) using the highly sensitive technique of therapeutic drug monitoring. [2][3][4][5] Despite the enormous burden of non-adherence to the health care system, practical and reliable methods of adherence detection are not well developed. Adherence can be monitored by several methods such as patient self-report, detailed questionnaire, pill counts, prescription fill rate, or electronic pillboxes.…”
Section: Introductionmentioning
confidence: 99%